Evaluation of Free Radical Scavenging Efficacy of Siddha Formulation Pirandai uppu Using in vitro Antioxidant Assay - Selvakumaran, Kanimozhi; Rajadhinakaran, Sathish Adithya; Elangovan, Nandhini; H, Subhashree (Free Radicals and Antioxidants)
Background: Concentrated forms of the plant extracts such as sathu/uppu possess effective medicinal properties. On concentrating the active principles were also get doubled. These organic substances are valuable resources for contemporary drug research. Pirandai uppu is the salt/ash extracted from Cissus quadrangularis. Pirandai uppu is used to cure a number of illnesses, including hemorrhoids, peptic ulcers, arthritis and diarrhea. Hence, the present study aims to assess the antioxidant property of Pirandai uppu from various antioxidant assays. Materials and Methods: The antioxidant properties of Pirandai uppu were assessed using DPPH, Nitric Oxide Radical Scavenge Assay, ABTS and Hydrogen Peroxide Radical Scavenge Assay. Percentage of inhibition and IC50 values were calculated and compared with that of standards. Results: The percentage inhibition of Pirandai uppu from DPPH radical scavenging activity ranges from 15.935±4.314 to 78.45±18.05%, The percentage inhibition of Pirandai uppu from NO radical scavenging activity ranges from 23.28±6.137 to 70.26±8.898%, The percentage inhibition of Pirandai uppu from ABTS radical scavenging activity ranges from 15.72±24.67 to 75.16±22.1% and The percentage inhibition of Pirandai uppu from hydrogen peroxide radical scavenging activity ranges from 16.234±0.9669 to 68.87±0.9743%. Conclusion: The siddha formulation Pirandai uppu has promising free radical scavenging activity in the estimated assays. Thus, Pirandai uppu posses a potent antioxidant property. This may be due to rich flavonoid content in Cissus quadrangularis.
Keywords: Antioxidants; Pirandai uppu; Siddha; Free Radicals